6th International Conference on Cucurbiturils (ICCB2019): Athens, Ohio, USA, July 21-24th. Issue 6 (2nd June 2020) - Masson, Eric; Urbach, Adam R.
ABSTRACT: The most recent International Conference on Cucurbiturils (ICCB) was held at Ohio University in Athens, Ohio. The three-day meeting included the latest advancements in the basic and applied science of cucurbiturils and related cavitands, as well as presentations from related areas of supramolecular chemistry. Abstract :